2014
DOI: 10.1177/1687814020945920
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear dynamics behavior of cam-follower system using concave curvatures profile

Abstract: Nonlinear dynamics behavior of the roller follower is discussed for different follower guides’ internal dimensions and cam angular speeds. A dynamic tool such as Wolf algorithm is used to extract largest Lyapunov exponent parameter. Positive value of Lyapunov exponent parameter indicates non-periodic motion and chaos. The influence of flank curvature of the cam profile on the nonlinear dynamic behavior of the roller follower is investigated. Impulse and momentum theory is used to describe the impact phenomenon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Yousuf and Marghitu studied the influence of flank curvature of the cam profile on the nonlinear dynamic behavior of the roller follower at different cam speeds (N) and different follower guides' internal dimensions (F.G.I.D.). They concluded that the follower motion is non-periodic when the cross-linking of the phase-plane diagram diverges with no limit of spiral cycles by taking into consideration the impact through impulse and momentum theory, [11]. This study is an extension of previous studies in the field of nonlinear dynamics phenomenon in cam follower system.…”
Section: Introductionmentioning
confidence: 73%
“…Yousuf and Marghitu studied the influence of flank curvature of the cam profile on the nonlinear dynamic behavior of the roller follower at different cam speeds (N) and different follower guides' internal dimensions (F.G.I.D.). They concluded that the follower motion is non-periodic when the cross-linking of the phase-plane diagram diverges with no limit of spiral cycles by taking into consideration the impact through impulse and momentum theory, [11]. This study is an extension of previous studies in the field of nonlinear dynamics phenomenon in cam follower system.…”
Section: Introductionmentioning
confidence: 73%
“…The follower displacement is processed using MatLab software. 16 The value of the spring stiffness (k) between the follower and the installation table can be calculated from load-deflection diagram experimentally, as indicated in Figure 4. The results of applied load against spring deflection in Figure 4 is obtained from the experiment test.…”
Section: Experiments Testmentioning
confidence: 99%
“…All the springs and viscous damping coefficients have the same values in which (k 1 ¼ k 2 ¼ k 3 ¼ k 4 ¼ 7 N/mm), and the viscous damping coefficient (c 1 ¼ c 2 ¼ c 3 ¼ c 4 ¼ 0.875 N.s/mm). The spring with the elastic constant (k ¼ 38.0611 N/mm), and the preload extension (D ¼ 37 mm) 16 is added between the installation table and the follower stem since it absorbs the energy of the spiral orbits of the follower movement. SolidWorks software is used in the simulation of multi degrees of freedom system.…”
Section: Multi Degrees Of Freedom Of Systemmentioning
confidence: 99%